One new species of the genus Acosmetura (Orthoptera: Tettigoniidae: Meconematinae) from Hunan, China - Chen, Chun; Xu, Hao; Shi, Fuming (Zootaxa, 2023)
This paper reports one new species of the genus Acosmetura Liu, 2000, i.e., Acosmetura compressa sp. nov. from Hunan, China. In addition, morphological photographs of the new species and a distribution map of the known species of the genus are provided. The type specimens are deposited in the Museum of Hebei University.